Pandangan Ibnu Khaldun dan Adam Smith Tentang Mekanisme Pasar - Indra Hidayatullah (IQTISHODUNA: Jurnal Ekonomi Islam, 2018)
Markets, countries, individuals and societies are always a hot topic of discussion in economics The passage of a market will be determined by several factors, first of price, demand and supply, distribution and specialization of workers, which when the above factors go according to the rules in the country, then it can be sure the economy in the country will be stable. The real good state economy is driven by market mechanisms that uphold freedom and justice, hence the market is free and impartial. In the history of economics in the world emerged some Islamic and conventional economists who raised the theme of science about market mechanisms, such as Ibn Khaldun and and Adam Smith. Ibn Khaldun examines the economic problems by examining the causes empirically, comparing them, and then summarizing the laws that explain the phenomenon. Thus he can be called as the originator of the first scientific economy. It was only about four centuries later after the death of Ibn Khaldun, European scientists apply the same method. The person who did it was Adam Smith. Ibn Khaldun lived in 732 to 808 H is one of the Muslim scholars who also helped spawn the concept of Islamic economic thinking. He is more popular as Ibn Khaldun. Ibn Khaldun examines the economic problems of society and state empirically, he explains the actual economic phenomena, as he expressed in his Muqaddimah. Adam Smith is one of the leading liberal economists who adhere to the laissez faire principle or liberation in economics. He is a figure who diligently popularize his free market to the public. In his economic theory, Smith considers that free markets are a necessary condition for economic growth